2014
DOI: 10.1063/1.4870280
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed magnetic field measurement system based on colossal magnetoresistance-B-scalar sensors for railgun investigation

Abstract: A high pulsed magnetic field measurement system based on the use of CMR-B-scalar sensors was developed for the investigations of the electrodynamic processes in electromagnetic launchers. The system consists of four independent modules (channels) which are controlled by a personal computer. Each channel is equipped with a CMR-B-scalar sensor connected to the measurement device-B-scalar meter. The system is able to measure the magnitude of pulsed magnetic fields from 0.3 T to 20 T in the range from DC up to 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…The software recalculates the measurement data of each connected sensor by applying the corresponding calibration data and displays the measurement signals. More detailed information about the CMR-B-scalar sensor system can be found in [18] and [21].…”
Section: B the Cmr-b-scalar Sensor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The software recalculates the measurement data of each connected sensor by applying the corresponding calibration data and displays the measurement signals. More detailed information about the CMR-B-scalar sensor system can be found in [18] and [21].…”
Section: B the Cmr-b-scalar Sensor Systemmentioning
confidence: 99%
“…However, the data obtained suffered from electromagnetic interference. Therefore, the measurement system was considerably improved to gain a better signal quality [18]. This paper describes the continuation of the work presented in [16] and [17].…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic decoupling is thought to be the result of interfacial effects of grains and depends on grain boundary (GB) material which might be assumed as ferromagnetic regions with suppressed magnetic order [11] due to a high number of various defects, created during film deposition process. It was demonstrated [7] that long-term storage of thin polycrystalline films and post-annealing has also a significant influence on the demagnetization field of these films.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason the temperature drift during operation of the CMR-B-scalar sensors is very important and has to be taken into consideration during design of such devices. This problem is solved by measurement of film's resistance in zero magnetic field just before the application of pulsed magnetic field which has to be measured [7]. In such case zero-field resistance of the film is a measure of ambient temperature while the resistance change in applied magnetic field is a measure of magnitude of this field.…”
Section: Introductionmentioning
confidence: 99%
“…R ECENTLY, it was demonstrated that nanostructured (nanograined polycrystalline) La 1−x Sr x MnO 3 (LSMO) films which exhibit the colossal magnetoresistance effect (CMR) can be successfully used for the development of CMR-B-scalar sensors [1], [2]. These small-volume sensors allow for measurements of absolute magnitude of magnetic flux density B, in the time scale of milliseconds, during high magnetic field pulses.…”
Section: Introductionmentioning
confidence: 99%